Sastra di Sekolah - Sapardi Djoko Damono (HISKI, 2007)
Today, the teaching of literature in schools is part of the teaching of the Indonesian language. Perhaps, due to the prevailing assumption that anything that is taught at schools should be scientific, all of the text books on literature for secondary schools are full of concepts, terms, lists of works, biography of authors and so on, which more often than not, take away much of the valuable time for the enjoyment of reading the work. In this paper the author argues that literary appreciation demands that students read literary works. However, there are three other problems related to, namely, reading material, selection of works worth reading, and the status and function of teachers in the appreciation process.